MAPPING THE PRIVATE SPACE OF THE ROMANIAN CONSUMER: MICRO AND MACROECONOMIC IMPLICATIONS - VAGHEȘ, Călin; POPESCU, Ioana Cecilia; ORZAN, Mihai; ACATRINEI, Carmen (Annales Universitatis Apulensis Series Oeconomica, 2014)
According to the Law No. 677/2001 on the Protection of Individuals with Regard to the Processing of Personal Data and the Free Movement of Such Data, any information referring to an identified or identifiable person, particularly with reference to an identification number or to one or more specific factors of his physical, physiological, economic, cultural or social identity is defined as personal data. An analysis of the consumers' perceptions regarding the processing and protection of their personal data reveals that almost anything may be associated to an individual and becomes personal, but not anything personal deserves a protection as described by the law. The paper presents the results obtained through a survey conducted on a sample of 394 Romanian consumers and discusses the micro and macroeconomic implications of mapping the consumer private space.